2019
DOI: 10.26725/jee.2019.3.31.6343-6348
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation and Marketing Knowledge level of Areca nut Farmers in Andaman & Nicobar Islands

Abstract: Areca nut (Areca catechu L) also known as betel nut or supari is the second most important plantation crop of Andaman and Nicobar Islands (ANI) after coconut It has been observed that wide differences in productivity of areca nut exist among the farmers with in a village due to socio-economic status. A survey based study was conducted to understand the knowledge level of areca nut growers and link to productivity vis-a-vis socio-economic status. For this purpose, 120 areca nut farmers from four villages of Har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Badhe & Tambat (2009) reported that more than three-fourths of respondents faced a major constraint in cultivating intercrops causing decrease in the yield of nuts and transmission of disease from intercrop. Arecanut is grown mostly by marginal and small farmers with less than 2.0 hectares of land (Kasinath et al, 2019) and needs less maintenance. Thus, the identification of constraints in arecanut cultivation helps to address the constraints faced by farmers in both production and marketing, and to increase the area of arecanut.…”
mentioning
confidence: 99%
“…Badhe & Tambat (2009) reported that more than three-fourths of respondents faced a major constraint in cultivating intercrops causing decrease in the yield of nuts and transmission of disease from intercrop. Arecanut is grown mostly by marginal and small farmers with less than 2.0 hectares of land (Kasinath et al, 2019) and needs less maintenance. Thus, the identification of constraints in arecanut cultivation helps to address the constraints faced by farmers in both production and marketing, and to increase the area of arecanut.…”
mentioning
confidence: 99%